2015
DOI: 10.1186/s12876-015-0254-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of serum triglyceride elevation at early stage of acute biliary pancreatitis

Abstract: BackgroundPancreatitis induced by hypertriglyceridemia (HTG) has gained much attention. However, very limited numbers of studies have focused on the clinical significance of TG elevation in non-HTG induced pancreatitis, such as acute biliary pancreatitis (ABP). This study aimed to study the clinical significances of triglyceride (TG) elevation in patients with ABP.MethodsWe retrospectively analyzed a total of 426 ABP cases in our research center. According to the highest TG level within 72 h of disease onset, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 31 publications
2
21
1
1
Order By: Relevance
“…TC, L-DL, and high levels of diabetes B were not associated with gallstones. Previous studies on the relationship between cholesterol and LDL and gallstones were contradictory, and several cross-sectional studies were reported as reverse [22,23], positive [24][25][26], and ineffective [27,28], Several prospective studies of gallstones were not associated with TC and/or low-density lipoprotein [29,30]. The reasons for these inconsistencies are unclear but may be due to differences in research design, research population, lipid measurement methods, or mixed control deficiencies.…”
Section: Discussionmentioning
confidence: 99%
“…TC, L-DL, and high levels of diabetes B were not associated with gallstones. Previous studies on the relationship between cholesterol and LDL and gallstones were contradictory, and several cross-sectional studies were reported as reverse [22,23], positive [24][25][26], and ineffective [27,28], Several prospective studies of gallstones were not associated with TC and/or low-density lipoprotein [29,30]. The reasons for these inconsistencies are unclear but may be due to differences in research design, research population, lipid measurement methods, or mixed control deficiencies.…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 ] Elevated triglyceride levels have been shown to increase the severity and mortality in biliary pancreatitis. [ 6 ] In a study by Navarro,[ 7 ] HTGP patients had more severe disease and more complications than patients with biliary pancreatitis. Heavy alcohol intake is also a risk factor for the development of HTG and it has been suggested that alcohol use be stopped in patients with concurrent HTG.…”
Section: Introductionmentioning
confidence: 99%
“…Hypertriglyceridemia (HTG) accounts for 1 to 4 percent of cases of acute pancreatitis [ 8 , 9 ]. On the other hand, HTG is commonly present at the early stage of non-HTG-induced AP and its clinical significance remains unclear [ 10 ].…”
Section: Introductionmentioning
confidence: 99%